2013
DOI: 10.1016/j.ijscr.2013.01.032
|View full text |Cite
|
Sign up to set email alerts
|

Transmesenteric hernia: A rare cause of bowel ischaemia in adults

Abstract: Close monitoring of the patient's general condition in cases of non-specific abdominal pain is essential to identify the rare deteriorating patient for early surgical intervention and optimal outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 16 publications
0
21
0
Order By: Relevance
“…These mesenteric vessels form a very complex network with several small branches including the caudal pancreatico‐duodenal branches, jejunal branches, ileal branches, ileocolic branches, right colic branches, middle colic branches, left colic branches, and cranial rectal branches, and have wide variations in dogs and cats . Deterioration of mesenteric circulation can induce ischemia of the small intestine, and mesenteric volvulus, intussusception, mesenteric internal hernia of the small intestine, and abdominal trauma can result in complete or partial obstruction of the mesenteric vessels and eventual intestinal necrosis . Mesenteric vascular thrombosis can be associated with disseminated abdominal tumors such as hemangiosarcoma, or various underlying diseases including hypertrophic cardiomyopathy, hepatopathy, protein‐losing nephropathy, or corticosteroid imbalance in dogs and cats .…”
Section: Introductionmentioning
confidence: 99%
“…These mesenteric vessels form a very complex network with several small branches including the caudal pancreatico‐duodenal branches, jejunal branches, ileal branches, ileocolic branches, right colic branches, middle colic branches, left colic branches, and cranial rectal branches, and have wide variations in dogs and cats . Deterioration of mesenteric circulation can induce ischemia of the small intestine, and mesenteric volvulus, intussusception, mesenteric internal hernia of the small intestine, and abdominal trauma can result in complete or partial obstruction of the mesenteric vessels and eventual intestinal necrosis . Mesenteric vascular thrombosis can be associated with disseminated abdominal tumors such as hemangiosarcoma, or various underlying diseases including hypertrophic cardiomyopathy, hepatopathy, protein‐losing nephropathy, or corticosteroid imbalance in dogs and cats .…”
Section: Introductionmentioning
confidence: 99%
“…Although usually within normal range, leukocyte count may increase and metabolic acidosis may develop in the case of development of intestinal gangrene. The cases in the literature were generally admitted to hospital with symptoms of intestinal obstruction and strangulation and most of them needed a resection and anastomosis of bowel (15). However, in our case, the patient was admitted to the hospital with the symptoms of acute appendicitis.…”
Section: Discussionmentioning
confidence: 73%
“…We report a case of bowel obstruction with caecal ischaemia due to an internal hernia caused by a congenital transverse mesenteric defect in an adult patient, initially misdiagnosed on CT as congenital midgut malrotation. Acute bowel obstruction secondary to internal hernia from a congenital mesenteric defect is extremely rare with only a few reported cases in the literature 1. To the authors' knowledge, this is the first reported case of internal hernia secondary to a congenital mesenteric defect in an adult patient resulting in colonic involvement and caecal ischaemia.…”
Section: Figurementioning
confidence: 79%